DEVELOPING ALTERNATIVES: CITIZENS PERSPECTIVES ON CAUSES AND THE RAMIFICATIONS OF THE 2003 CONFLICT IN DARFUR - Yaro, David Suaka; Felix , Longi (International Journal of Conflict Management, 2022)
This manuscript provides an alternative examination of the causes and the ramifications of the conflict in Darfur. The findings reveled the causes of the conflict to be religion, racial segregation, resources, geographical factors, the influx of weapons etc. and the ramifications are Genocide/Killing, Starvation, Rape, Fear and insecurity, Destruction of Property etc. The parties involved are Government forces, Janjaweed, USA, China Libya, Egypt etc. A purposive sampling technique was used to select 26 respondentswhich include, Diplomats, Civil Servants, Students and refugees. The instrument used for data collection was a semi-structured interview guide. It was conducted within the framework of "˜identity politics. The recommendation to the Sudanese Government is that the government has the following role to play: Protection of the civilian population by the Sudanese government. This can be done by: Publishing and disseminating orders eliminating the targeting of inhabitants, properties and indiscriminate attacks,and enforcement of orders prohibiting the targeting of civilians and civilian property and indiscriminate attacks. Publicise and enforce a policy that embraces zero tolerance for violence against women. Enforcement of UN/ AU Resolutions: The Security Council veto on invasive military flights must be enforced. The AU and NATO should agree on enforcement processes to be applied if Khartoum violates the injunction in United Nation Security Council Resolution 1591 and National Reconciliation: There should be reconciliation that comprises of prosecution of perpetrators of atrocities, the safe return of villagers to their villages and violence compensation.